Chair Perceptions of Trust between Mentor and Mentee in Online Doctoral Dissertation Mentoring - Rademaker, Linnea (Online Learning, 2016)
We explored online dissertation chairs’ perceptions of trust in the mentor—mentee relationship, as trust was identified as a crucial factor in the success of doctoral students. Through the implementation of a multiple-case study, and a qualitative, online questionnaire, and through qualitative data analysis, we discovered 16 chairs’ perceptions of trust and that student vulnerability is an important part of the relationship that chairs consistently work to alleviate. Findings point to the importance for chairs to establish trust through feedback, consistency, and personal connections with students. Second, chairs perceived student vulnerability to include both students’ discussion of their academic skills (or lack thereof) and their willingness to share personal information. Chairs were very resourceful in enacting strategies to alleviate all types of student vulnerability, including recognizing student strengths and pointing to the positives of vulnerability and by offering scholarly resources for students to develop their academic strengths.